The Mechanism and Benefits of Receiving Government Facilities in Bonded Zone for Tax and Financial Report: A Case Study - Putri, Shafa Alika; Prihatiningtias, Yeney Widya (Telaah Ilmiah Akuntansi dan Perpajakan, 2023)
This research aims to find out more about the mechanism and benefits of the Bonded Zone Facility. A qualitative research approach was adopted to explore the mechanism of obtaining this facility and the benefits for the manufacturing companies, involving interviews, documentation analysis, and case studies. The interview was conducted online by interviewing sources from PT X’s Bonded Zone Team, which are Informant LR, Informant ESP, and Informant MR. The research findings indicate that the mechanism to obtain the Bonded Zone facility is governed by the rules outlined in the Directorate General of Customs and Excise number PER-19/BC/2018. Companies interested in getting the facility must fulfill the requirements specified in these rules and register as Entrepreneurs in The Bonded Zone (PDKB). The benefits of receiving the Bonded Zone facility can be classified into two aspects: financial and operational. The company can reduce costs from a financial perspective due to the deferred import duty and exemptions of Value-Added Tax and Income Tax Article 22 for Import. In conclusion, the Bonded Zone facility in Indonesia offers significant advantages for export-oriented manufacturing companies. Through the mechanism outlined in the Directorate General of Customs and Excise rules, eligible companies are subject to financial benefits through tax exemptions and deferrals, as well as operational benefits by eliminating the need for customs clearance and enabling the direct unloading of goods. These benefits enhance manufacturing companies' competitiveness in the global market and stimulate the Indonesian economy.   Abstract Penelitian ini ditujukan untuk mengetahui lebih lanjut terkait Mekanisme dan Manfaat Penerima Fasilitas Kawasan Berikat. Metode dalam penelitian ini menggunakan metode kualitatif dan pengambilan data dilakukan dengan cara wawancara, pengambilan dokumen, serta studi kasus. Wawancara akan dilakukan dengan mewawancarai tiga narasumber dari tim Kawasan Berikat dari PT X, yaitu informan LR, informan ESP, dan MR. Penelitian ini dilakukan secara daring dengan menggunakan aplikasi Google Meet. Hasil dari penelitian ini adalah bahwa mekanisme mendapatkan fasilitas Kawasan Berikat diatur dalam Peraturan Direktur Jenderal Bea dan Cukai Nomor PER-19/BC/2018 yaitu dengan mengajukan permohonan dan persyaratan yang diperlukan dalam peraturan tersebut serta mendaftarkan pengusaha sebagai Pengusaha Kawasan Berikat (PDKB), lalu menunggu hasil pengecekan lapangan dari Kantor Wilayah Bea dan Cukai setempat sehingga akhirnya perusahaan bisa menjadi penerima fasilitas Kawasan Berikat. Keuntungannya ada dalam dua aspek, keuangan dan operasional. Dalam aspek keuangan, perusahaan dapat menghemat dana karena adanya penangguhan Bea Masuk dan tidak dipungutnya PPN dan PPh Pasal 22 Impor. Sementara untuk aspek operasional, pengusaha dapat menghemat waktu tanpa harus menempuh customs clearance sehingga barang dapat dibongkar di pabrik atau gudang perusahaan manufaktur tersebut.